Galvanic Corrosion of Orthodontic Brackets and Wires in Acidic Artificial Saliva: Part II - Sheikh, Tahereh; Ghorbani, Mohammad; Tahmasbi, Soodeh; Yaghoubnejad, Yadollah (Journal of Dental School, 2019)
Objective: Orthodontic wires should have high resistance against corrosion in the oral environment. Since the effect of pH on corrosion has been well recognized, this study sought to assess and compare the electrochemical corrosion of orthodontic brackets and wires of different brands in acidic artificial saliva. Methods: This in vitro experimental study was conducted on 24 mandibular central incisor brackets of 4 manufacturers namely Dentaurum, American Orthodontics, Shinye and ORJ. The brackets were immersed in acidic artificial saliva along with stainless steel (SS) or NiTi 0.016 round wires for 28 days. All specimens were weighed before and after the experiment by a digital scale. After the experiment, the specimens were evaluated under a light stereomicroscope and specimens with corrosion were further assessed by scanning electron microscope (SEM) and energy-dispersive X- ray spectroscopy (EDX). Two-way ANOVA was used for statistical analysis. Results: The mean corrosion rate (CR) was -1.80, 0.11, 0.05 and -0.93 mpy for Dentaurum, American Orthodontics, Shinye and ORJ brackets, respectively in combination with NiTi wire; these values were 0.46, -0.71, 0.87 and -0.27 mpy, respectively in combination with SS wires; the differences in this regard were not statistically significant (p>0.05). Micrographs showed high corrosion in ORJ brackets followed by Shinye brackets. EDX showed that the combination of ORJ bracket with SS wire had the highest iron (Fe) content and the highest CR. Conclusion: SS brackets manufactured by Shinye and ORJ companies in combination with SS wires showed higher CR in acidic artificial saliva compared to other bracket/wire combinations.